Differences in nutritional quality of milk produced from ewes reared in mountain versus valley areas - Bravo-Lamas L.; Aldai N.; Kramer J.K.G.; Barrón L.J.R. (Mountain pastures and livestock farming facing uncertainty: environmental, technical and socio-economic challenges, 2016)
In the present study, fat content and fatty acid (FA) composition of milk from ewes reared in valley and mountain pastures was investigated. Six flocks of Latxa ewes were selected (3 from valley and 3 from mountain) and milk was collected in triplicate in May and June, during the grazing period at late lactation. Mountain milk was fatter than valley milk (p≤0.001). Interaction between pasture type and sampling week was significant (p≤0.05) for saturated FA (SFA), monounsatured FA (MUFA), conjugated linolenic acid (CLA) and non-conjugated dienes, where mountain milk provided less SFA, more MUFA, and more CLA, mainly 9cis(c), 11trans(t)-18:2. Looking closer at the nutritionally interesting FAs, in all milk samples 11t-18:1 was the major trans-18:1 isomer (average of 55.6%), while the 10t-/11t- ratio was below 1 in all milk samples. In addition, mountain milk samples provided higher values (p≤0.001) for branched-chain FA, cis-MUFA and polyunsaturated FAs (PUFA) content, and higher P/S ratio. In general, mountain milk provided higher contents of metabolites related to the biohydrogenation n-3 PUFA like 9c,11t,15c-18:3, 11t,15c-18:2 and 11t,13c-18:2 and a lower n-6/n-3 ratio. Therefore, the milk from ewes reared in the mountain grasslands had a healthier FA profile and could provide value-added cheese of commercial benefit.
19. Meeting of the FAO-CIHEAM Mountain Pastures Subnetwork, 2016/06/14-16, Zaragoza (Spain)